Front Cover: Stability of Metallic Current Collectors in Acidic Ionic Liquid for Rechargeable Aluminum‐Ion Batteries (ChemElectroChem 22/2018). Issue 22 (12th October 2018) - Oh, Youngho; Lee, Gibaek; Tak, Yongsug
Abstract : The Front Cover illustrates the concept of finding the last piece of the puzzle to complete rechargeable aluminum‐ion batteries as one of the future advanced energy storage systems. More information can be found in the Communication by Y. Oh et al. onpage 3348 in Issue 22, 2018 (DOI:10.1002/celc.201800892 ).